Implementasi Konsep Family Park pada Perancangan Interior Intergenerational Activity Center di Surabaya - Felita Fernanda; Diana Thamrin; Lucky Basuki (Intra, 2018)
Surabaya is known as a city with its residents who have various activities and focus on pursuing their career. As we enter the women’s emancipation era, now women also give their contribution by doing some of the works that men usually do. Many parents tend to forget the importance of a family; meanwhile, the role of parents is very significant for the child development. Third parties, such as child care has acted as parents’ destinations everyday as they put more focus on their jobs. Intergenerational Activity Center will provide solutions towards the problems stated above. This facility will act as a bridge between the needs of parents and their children which at the same time will enable the parents to take care of their children and do their jobs. The design method includes 7 stages, which are Define, Research, Ideate, Prototype, Select, Implement, and Learn. The result will be a complete facility for family with Family Park concept which offers fun, relaxing, and comfortable atmosphere for both the parents and their children. It will provide the core areas which are needed by most parents, such as working and reading spaces, canteen or restaurant, as well as sport facilities. Moreover, this facility offers educational entertainment for children since they will be able to enjoy the toys and games which emphasizing on educational purposes.